Public Relations Strategy of the National Family Planning Coordinating Board (BKKBN) in Socializing the Family Planning (KB) Program in Kec. Tarowang, Jeneponto Regency - Muh Fahmi Jamaluddin; Akhmad, Akhmad; Andi Risfan Rizaldi (CV. AFDIFAL MAJU BERKAH, 2024)
The purpose of this study was to determine BKKBN in Socializing Family Planning (KB) Programs in Tarowang District, Jeneponto Regency. This type of research is qualitative. The type of data used in this study is qualitative data obtained from interviews with several informants. Data collection is done by observation, interviews and documentation. In this study, the data sources used in data collection include primary data and secondary data. The research instrument used in this study is interview guidelines. Based on the results of the research that has been conducted, the conclusion of this study is to explain that the strategy of the national family planning coordinating board (BKKBN) in socializing family planning (KB) programs in Tarowang District, Jeneponto Regency consists of several stages. First, BKKBN conducts audience analysis by understanding the characteristics and needs of local communities through surveys and data collection. Furthermore, BKKBN chooses the right communication method, composes messages clearly and according to the needs of the audience, and chooses diverse and appropriate communication strategies. The use of outdoor media such as banners and stickers is carried out in BKKBN's efforts to convey messages about family planning to the community effectively.